Factors Related To Anxy Events In Diabetes Mellitus Type 2 In Public Health Center - Ira Inayah; Aszrul AB; Edison Siringoringo; Nurlina (Comprehensive Health Care, 2020)
Tuberculosis is a contagious disease caused by the bacteria Mycobacterium Tuberculosis which is spread through droplets of people who have been infected with tuberculosis bacilli. Pulmonary tuberculosis is still a challenge in public health problems both regionally, nationally, and globally. According to the World Health Organization (WHO) in 2015, there were 10.4 million new TB cases and nearly 75% of pulmonary tuberculosis patients were economically productive age groups. . The purpose of this study was to determine the physical environmental factors of the house with the incidence of pulmonary tuberculosis at the Bonto Bahari Health Center in 2020. The research method used was using analytical research methods with a case-control approach (case-control) where subjects, namely cases and controls were known and selected based on the output ( out came), then looked back (backward) about the history of the research exposure status experienced by the subject. The population in this study was about 40 people and the sample in this study amounted to 80 because the researcher took 40 controls. The results of the analysis using the Wilcoxon and Mc Nemar tests, with the results obtained by the value of ventilation (p-value = 0.001) then Ho is rejected and Ha is accepted. The type of floor obtained value (p-value = 1,000) then Ho is accepted and Ha is rejected. The type of wall obtained value (p-value = 0.002) then Ho is rejected and Ha is accepted. Occupancy density obtained value (p-value = 0.582) then Ho is accepted and Ha is rejected. The conclusion of this study There is a relationship between ventilation and the incidence of pulmonary tuberculosis, there is a relationship between the type of wall and the incidence of pulmonary tuberculosis and there is no relationship between floor type and occupancy density with the incidence of pulmonary tuberculosis.